UPAYA GURU FIQIH DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA MENGGUNAKAN METODE RESITASI DI KELAS VIII MTs MATHLAUL ANWAR PASAR KEMIS KABUPATEN TANGERANG - Faturrohman, Muhammad Fahri; Basyit, Abdul; Gumelar, R Tommy; Kusni, Nikmatullah (Universitas Muhammadiyah Tangerang, 2025)
AbstractThe purpose of this study was to determine the efforts of fiqh teachers in increasing student motivation using the recitation method, to find out the implementation of the recitation method in fiqh subjects, to determine the effectiveness of applying the recitation method to fiqh class VIII subjects at MTs Mathlaul Anwar Pasar Kemis. This study uses a type of qualitative research, data collected from interviews, field notes, personal documents and other documents. The data collected by the author of the analysis using descriptive analysis techniques. The results of the research show that the efforts of the fiqh teacher in increasing learning motivation are choosing the right teaching method, having a teaching strategy, having a goal in using the recitation method. The implementation of the recitation method is carried out in three phases, namely the assignment phase, the implementation phase, the assignment accountability phase. The effectiveness of the recitation method in fiqh subjects in Class VIII MTs Math’laul Anwar Pasar Kemis is quite effective considering that there are not so many study hours but the material delivered is quite a lot. Keywords: Recitation Method, Learning Motivation, Teacher Effort